The contribution of e-HRM to HRM effectivness / Amiza Raizan Abdul Raof ...[et al] - Abdul Raof, Amiza Raizan (Faculty of Business and Management, 2013)
Using the resource-based view of the HRM, this study examines the effective use of e-HRM on organizational performance. Results show that e-HRM effectiveness significantly increases the employee's performance and HR effectiveness. E-HRM is coming to a more full-grown stage within organizational life. In this paper we present results from the first quantitative study on the contribution of e-HRM to HRM effectiveness. The data is collected in a Kementerian Kemajuan Luar Bandar & Wilayah (KKLW). Results show that actual use, quality and job relevance of the e-HRM application correlates with HR effectiveness, especially the content and design (quality of the e-HRM application). Results indicate that the level of e-HRM relevant to the HRM effectiveness. In the final section of the paper conclusions are drawn, limitations discussed and future research directions raised.